Cross Testicular Ectopia - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Cross testicular ectopia is an extremely rare congenital anomaly affecting male children. It is a deviation of testicular descent resulting in unilateral location of both testes which poses a problem in diagnosis and treatment among clinician in the world. Over a period of 4years 4 cases of testicular ectopia were managed by our unit. All of our patients presented as outpatient. The record of their presentation, surgical management and the outcome of the treatment were studied and documented. The age ranges between 2 to 6years. All of the patients had trans septal orchidopexy as a day case surgery. Cross testicular ectopia is rare congenital urologic condition but the outcome of its management seem to be good, however long term follow up is required to evaluate the testicular function.